Fluid inclusion, zircon U-Pb geochronology, and O-S isotopic constraints on the origin and evolution of ore-forming fluids of the tashvir and varmazyar epithermal base metal deposits, NW Iran - Kouhestani, Hossein; Mokhtari, Mir Ali Asghar; Chang, Zhaoshan; Qin, Kezhang; Aghajani Marsa, Soheila (Frontiers in Earth Science, 2022)
Tashvir and Varmazyar deposits are part of the epithermal ore system in the Tarom–Hashtjin Metallogenic Belt (THMB), NW Iran. In both deposits, epithermal veins are hosted by Eocene volcanic-volcaniclastic rocks of the Karaj Formation and are spatially associated with late Eocene granitoid intrusions. The ore assemblages consist of pyrite, chalcopyrite, chalcocite, galena, and sphalerite (Fe-poor), with lesser amounts of bornite and minor psilomelane and pyrolusite. Fluid inclusion measurements from the Tashvir and Varmazyar revealed 182–287 °C and 194–285 °C formation temperatures and 2.7–7.9 and 2.6–6.4 wt.% NaCl equivalent salinities, respectively. The oxygen isotope data suggested that the mineralizing fluids originated dominantly from a magmatic fluid that mixed with meteoric waters. The sulfur isotope data indicated that the metal and sulfur sources were largely a mixture of magma and surrounding sedimentary rocks. LA-ICP–MS zircon U–Pb dating of the granitoid intrusion at Tashvir and Varmazyar, yielded a weighted mean age of 38.34–38.31 and 40.85 Ma, respectively, indicating that epithermal mineralization developed between 40.85–38.31 Ma. Our data indicated that fluid mixing along with some fluid boiling were the main drives for hydrothermal alteration and mineralization at Tashvir and Varmazyar. All these characteristics suggested an intermediate-sulfidation epithermal style of mineralization. The THMB is proposed to be prospective for precious and base metal epithermal mineralization. Considering the extensional tectonic setting, and lack of advanced argillic lithocaps and hypersaline fluid inclusions, the THMB possibly has less potential for economically important porphyry mineralization.